2020
DOI: 10.1182/blood-2020-140422
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of a Novel Anti-Human CD117-Amanitin Antibody Drug Conjugate (ADC) Engineered for a Short Half-Life Provides Dual Conditioning and Anti-Leukemic Activity and Extends Survival Compared to Standard of Care in Multiple Preclinical Models of Acute Myeloid Leukemia (AML)

Abstract: Hematopoietic stem cell transplant (HSCT) can be a highly effective, and often curative, treatment for patients with AML. At present, myeloablative conditioning (MAC) regimens are associated with severe acute and long-term toxicities. A subset of transplant-eligible AML patients undergoes reduced-intensity conditioning (RIC) regimens; while reducing toxicities, RIC regimens have higher incidence of post-transplant relapse and graft failure vs MAC. Thus, the need for safe and effective targeted conditioning age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Another group conjugated the CD117+ to amanitin (MGTA-117) and found it to be highly effective (it depleted more than 95% of HSPCs) in murine models that had acute myeloid leukemia (AML). CD117 is highly expressed in AML cells, and this regimen was found to decrease the tumour burden in these mice [ 203 ].…”
Section: Administration Of Gene-modified Hematopoietic Stem Cells: En...mentioning
confidence: 99%
“…Another group conjugated the CD117+ to amanitin (MGTA-117) and found it to be highly effective (it depleted more than 95% of HSPCs) in murine models that had acute myeloid leukemia (AML). CD117 is highly expressed in AML cells, and this regimen was found to decrease the tumour burden in these mice [ 203 ].…”
Section: Administration Of Gene-modified Hematopoietic Stem Cells: En...mentioning
confidence: 99%
“…Anti-CD117 has also been conjugated to amanitin, an RNA polymerase II inhibitor [ 59 61 ]. Amanitin is very hydrophilic, meaning that it does not readily enter cells.…”
Section: Antibody–drug Conjugates (Adcs)mentioning
confidence: 99%
“…The antibody was further developed by optimising the linker molecule and engineering a short half-life of 91 h in NSG mice. This ADC came to be known as MGTA-117 and exhibited > 95% depletion of host HSPCs in humanised mice [ 61 ]. MGTA-117 demonstrated anti-leukaemic activity, providing dual benefit as both conditioning and anti-cancer treatment.…”
Section: Antibody–drug Conjugates (Adcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of CD117 immunotoxin and ADC-based HSC depletion and conditioning has since been extended to human and rhesus macaque models. Specifically, Pearse et al and Lanieri et al have reported that an amanitin-based CD117-ADC effectively depleted normal and AML human HSCs and progenitors in vitro and in vivo in xenografts [179][180][181], in addition to showing safety and efficacy in non-human primates [210] with subsequent engraftment of autologous gene-modified hematopoietic stem cells in non-human primates as well [210]. Clinical testing of this agent recently began in a Phase 1 clinical trial with single-dose escalating cohorts in relapsed/refractory AML and MDS patients.…”
Section: Anti-cd117mentioning
confidence: 99%